Studies for Frost Heave Characteristics and the Prevention of the High-Speed Railway Roadbed in the Zoige Wetland, China - Niu, Fujun; Hu, He; Liu, Minghao; Ma, Qinguo; Su, Wenji (Frontiers in Earth Science, 2021)
The Xining–Chengdu high-speed railway crosses the Zoige Wetland, located on the northeast edge of the Qinghai-Tibet Plateau and the upper reaches of the Yellow River. The cold climate and frost-heave sensitive subgrade soil cause a large frost heave deformation of the roadbed, threatening the safety of trains. This paper systematically studied the ground temperature development, frost heave characteristics, soil water content, and groundwater level variations by field investigation and monitoring. The maximum frost heave deformations of the natural flat ground and hillslope reached 25.64 and 3.17 mm, respectively, and this significant discrepancy was mainly caused by the groundwater supply condition. Future roadbed stability on the flat ground may be compromised by frost heave deformation. To solve this problem, contrasting indoor tests were conducted to analyze the frost heave characteristics of natural ground clay and replacement coarse-grained soil (CGS). It was shown that the absorbed external water mainly changed into dispersed pore ice in the freezing CGS, while it mainly changed into the layered ice lens in the freezing clay. Further tests showed that the frost susceptibility of the CGS was proportional to the fines content and initial water content. The poorly graded CGS had weaker frost susceptibility than the well-graded CGS. The results suggest that the anti-frost methods should be fully considered, including strict control of fines content and water content, priority of using poorly graded filling, and disruption of local water accumulation in filling layer.